IMPACT OF INDUSTRIAL AND MUNICIPAL DISCHARGES ON GROWTH COEFFICIENT AND CONDITION FACTOR OF MAJOR CARPS FROM LAHORE STRETCH OF RIVER RAVI - H. A. Shakir; J. I. Qazi (Journal of Animal and Plant Sciences, 2013)
River Ravi, Pakistan is just like a wastewater carrier due to anthropogenic activities. This study investigate the growth profile of Catla (C) catla, Cirrhinus (C) mrigala and Labeo (L) rohita netted from three downstream polluted sites; Shahdera: B, Sunder: C and head Balloki: D and compared with less polluted site, Siphon: A (control) upstream during low (winter) and high (post monsoon) flow seasons of river Ravi. Weight and total length of sampled specimens were not significantly different (P>0.05) in different seasons and sites. Condition factor (K) in C. mrigala was estimated as 0.97-1.05, L. rohita 1.03-1.18 and for C. catla 1.14-1.27. Log transformed regression were used to test the growth. Growth coefficient (b) were measured highest 3.19 and 3.16 in C. mrigala, 3.21 and 3.17 in L. rohita, 3.16 and 3.11 for C. catla at control site while lowest in C. mrigala 3.08 and 3.07, L. rohita 3.08 and 3.06, in C. catla 3.03 and 3.01 at site C during high and low flow respectively. The ‘b’ results (P<0.001) represented positive allometric growth pattern with lower value during low flow than high flow season in sampled species. Reduction in ‘b’ value in downstream polluted sites indicated adverse effect of aquatic pollution on fish growth. However, the last downstream sampling locality showed more or less stabilized situation with a small recovery as compared to third study area. Further large scale studies covering long distances downstream from the city Lahore may reveal pollutants stresses’ recovery level or otherwise situation of inhabitant fish species.
Keywords: Municipal sewage; industrial effluents; carp fish species; growth; river Ravi; Pakistan